Reversed phase thin layer chromatography of five co-administered drugs with surfactant modified solvent systems - Bhawani, Showkat Ahmad; Ali, Mohammad; Sharma, Sudhanshu (2009)
The chromatography of five co-administered drugs i.e. paracetamol, ibuprofen, diclofenac sodium, aspirin and ascorbic acid was performed on various reversed phase layers. The surfactant mediated solvent systems were used with various impregnated silica gel H layers for the chromatography of these five drugs. The various experimental conditions were optimized for the selection of optimum concentration of impregnants. The mutual separation of a mixture of paracetamol, diclofenac sodium and ibuprofen; and paracetamol, aspirin and ascorbic acid are achieved on various impregnated silica gel H layers, using surfactant mediated solvent systems containing n-hexane: 1% CTAB in MeOH: ethyl acetate: acetic acid, (13:1:4:2, v/v) and toluene: 1% CTAB in MeOH: n-propanol: formic acid, (14:1:3:2, v/v) respectively.